Approximation and Online Algorithms 7th International Workshop,WAOA 2009, Copenhagen Denmark, September 10-11, 2009. Revised Papers - Bampis, Evripidis; Jansen, Klaus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post workshop proceedings of the 7th International Workshop on Approximation and Online Algorithms, WAOA 2009, held in Copenhagen, Denmark, in September 2009 as part of the ALGO 2009 conference event. The 22 revised full papers presented were carefully reviewed and selected from 62 submissions. The workshop covered areas such as algorithmic game theory, approximation classes, coloring and partitioning, competitive analysis, computational finance, cuts and connectivity, geometric problems, inapproximability results, mechanism design, network design, packing and covering, paradigms for design and analysis of approximation and online algorithms, parameterized complexity, randomization techniques, real-world applications, and scheduling problems.
WAOA 2009 -- On the Competitiveness of the Online Asymmetric and Euclidean Steiner Tree Problems -- Extension of the Nemhauser and Trotter Theorem to Generalized Vertex Cover with Applications -- Price Fluctuations: To Buy or to Rent -- Approximation Algorithms for Multiple Strip Packing -- Approximating Frequent Items in Asynchronous Data Stream over a Sliding Window -- Longest Wait First for Broadcast Scheduling [Extended Abstract] -- The Routing Open Shop Problem: New Approximation Algorithms -- On the Price of Stability for Undirected Network Design -- Finding Dense Subgraphs in G(n,1/2) -- Parameterized Analysis of Paging and List Update Algorithms -- Online Scheduling of Bounded Length Jobs to Maximize Throughput -- On the Additive Constant of the k-Server Work Function Algorithm -- A (4?+??)-Approximation for the Minimum-Weight Dominating Set Problem in Unit Disk Graphs -- Guard Games on Graphs: Keep the Intruder Out! -- Between a Rock and a Hard Place: The Two-to-One Assignment Problem -- Scheduling and Packing Malleable Tasks with Precedence Constraints of Bounded Width -- Online Minimization Knapsack Problem -- Optimization Problems in Multiple Subtree Graphs -- Multi-Criteria TSP: Min and Max Combined -- Packet Routing: Complexity and Algorithms -- Minimal Cost Reconfiguration of Data Placement in Storage Area Network -- Competitive Multi-dimensional Dynamic Bin Packing via L-Shape Bin Packing.
Keywords: Computer science; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Computer graphics; Algorithms; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Computer Graphics; Data Structures; Algorithms